Double Layer Pixelate Checkerboard Optimization for Ultrawideband Radar Absorber With Light Weight and Optical Transparency - Shan, Hanyu; Jiang, Tao (IEEE transactions on electromagnetic compatibility, 2025)
An efficient low-profile design strategy for a multilayer metasurface is proposed in this work, based on which an ultrawideband absorbing metasurface with lightweight, optical transparency, and excellent radar absorber is created. First, we propose designing resistive patterns on both sides of the transparent substrates to simultaneously realize layer numbers' compression and resonant structure abundance. The variables of the structure to be optimized are determined, which are converted into 1-bit strings. Second, the progressive multilayer optimization strategy with genetic algorithm-particle swarm optimization algorithms and reverse initial population method is proposed to optimize the 1-bit string corresponding to the structural parameters. Distance between layers is also considered during the optimization process, avoiding a narrow bandwidth caused by poor coupling between layers. Finally, an absorbing unit cell with more than 90% absorption rate in 6.0-41.0 GHz is achieved after the optimization process. After the periodic array layout, the absorbing metasurface also achieves excellent 10 dB mono-static and mirror bistatic radar cross-section reduction under large oblique incident angle. A sample is fabricated and measured to verify that the optical transparent metasurface achieves ultrawideband absorption, which will also be used in the electromagnetic shielding in the future.